Perbandingan Pendapatan Usahatani Jagung Manis (Zea mays saccharata Sturt) Dengan Padi Sawah (Oryza sativa L ) Di Kelurahan Pisang Kecamatan Pauh Kota Padang - Mangasa Saogo; Dang Sri Chaerani; Gusriati (Jurnal Research Ilmu Pertanian, 2022)
This study aims as follows: 1) To analyze the income and efficiency of sweet corn farming with paddy fields in Pisang Village, Padang City. 2) To analyze the difference between sweet corn and lowland rice farming income in Pisang Village, Padang City. The basic research method is descriptive and comparative analysis and implementation with the survey method. The selection of this research location was carried out by purposive sampling, based on the consideration that Pisang Village is one of the villages that cultivate sweet corn with lowland rice in turns. The population in this study were sweet corn farmers with lowland rice in Pisang Village, Padang City. Sampling was done by purposive sampling technique (deliberately), ie farmers whose main job is sweet corn farming with lowland rice with a minimum land area of 0.1 ha which is harvested at the time of the study. The number of samples was set at 60 farmers, consisting of 30 sweet corn farmers and 30 lowland rice farmers for research using primary and secondary data analysis. The analytical methods used include comparative analysis of farm income with the concept of operating costs. Comparative analysis of farm income using t test. The research was conducted in May-June 2018. Based on the results of the study, it can be concluded that: 1). The average income earned by sweet corn farmers is Rp. 14,518,518,52/Ha 1 (one) planting season with R/C ratio, 2,41 while for paddy Rp. 14. 837,814, 17/ha per growing season with R/C ratio, 2.43. The results of the analysis of the difference in average income per respondent of sweet corn sample farmers (Rp. T table (29,0.05) = 1.6991